2017
DOI: 10.3390/su9030393
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics and Spatial Determinants of Urban Growth in Suzhou, China

Abstract: This paper analyzes the spatiotemporal dynamics of urban growth and models its spatial determinants in China through a case study of Suzhou, a rapidly industrializing and globalizing city. We conducted spatial analysis on land use data derived from multi-temporal remote sensing images of Suzhou from 1986 to 2008. Three urban growth types, namely infilling, edge-expansion, and leapfrog, were identified. We used landscape metrics to quantify the temporal trend of urban growth in Suzhou. During these 22 years, Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Numerous studies have supported that the regional socioeconomic development is not a closed system [48,50]. Thus, the loss of ESV can be affected by its factors and external situations in its surrounding area [69].…”
Section: Spatial Pattern Of Changes Of Esvmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have supported that the regional socioeconomic development is not a closed system [48,50]. Thus, the loss of ESV can be affected by its factors and external situations in its surrounding area [69].…”
Section: Spatial Pattern Of Changes Of Esvmentioning
confidence: 99%
“…However, the loss of natural resources appears to be the inevitable price of urbanization, while different development modes and investment levels can have varying impact on the ESV changes. In addition, regional development is not a random independent phenomenon or stationary process over space [48][49][50], while the changes between regions will have evident geographical dependence. Previous studies have confirmed that the positive spatial spillover effects of industry development play an important role in improving urbanization level [51,52], while spatial agglomeration will be one of the most significant characteristics in China's new urbanization development [53].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, in the process of rapid urbanization, the relationship between man and nature has been reshaped, and human production activities have greatly influenced land use transformation. Most studies have asserted that population growth, resident income, urbanization, industrialization, and other socioeconomic factors are the impetus for land use transformation [11,13,14,[19][20][21][22][23][24][25]. Additionally, the production activities of individuals were closely related to the institutional arrangements at a given time and place [11,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the self-organization and complexity of the land use system, the land use transformation characteristics and influence factors of different types of regions vary [11]. Land use change in economically developed cities [23,25,30,31] and suburbs with rapidly expanding urban land [19,24] is mainly driven by economic interests, and land use change demonstrates that the amount of urban construction land increases rapidly whilst the amount of cultivated land decreases rapidly. To pursue economic growth, land use change in underdeveloped areas [18,32] also demonstrates an increase in urban construction land, but on a smaller scale.…”
Section: Introductionmentioning
confidence: 99%
“…This mainly includes the CLUE-S analysis system, Cellular Automata (CA), and SLEUTH model. Researchers use the above UGB models to carry out empirical research on the delimitation of living space in villages and towns [35][36][37][38][39][40][41][42]. From these empirical studies, we found that the CLUE-S analysis system needs less data.…”
Section: Introductionmentioning
confidence: 99%